College Behind Bars Vis a Vis the School-To-Prison Pipeline: Cause and Effect - Frederick V. Engram Jr (Ali Khorsandi Taskoh, 2022)
Criminality and criminal mindedness are automatic qualifiers affixed to incarcerated or formerly incarcerated persons. Very rarely are individuals seen as human and as individuals who lived life as free persons prior to their convictions. Many are only seen as their offense and by the number stitched to their clothing. When I was informed that I would be teaching (CRCJ 4333) Institutional Corrections during the Spring 2021 semester I decided that I wanted to re-imagine how we would explore incarceration and incarcerated persons. Guided by the theories of causation and critical race theory I assert that we must focus on the cause and effect associated with offending as well as the stories associated with those labeled "offenders". Many aspects of carceral research focus on understanding the offense but many lack the empathy to explore the root. This is largely because the root of crime and criminality in many cases concerning marginalized communities is tied to survival. Surviving white supremacy and surviving the communities that white supremacy imprisoned them in. This article will take a qualitative approach to understanding the lived experiences of the formerly incarcerated and how the 19 students enrolled in the course engaged with them.